Branches & Subfields of Geology - Vance, Treasa, author 640151 (Delhi, India : Learning Press, 2012)
The field of geochemistry involves study of the chemical composition of the Earth and other planets, chemical processes and reactions that govern the composition of rocks, water, and soils, and the cycles of matter and energy that transport the Earth's chemical components in time and space, and their interaction with the hydrosphere and the atmosphere.